2018
DOI: 10.2495/sdp180271
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Smart Farmers’ Perceptions Towards the Asean Economic Community

Abstract: The establishment of the ASEAN Economic Community (AEC) is a major milestone for Southeast Asia. This establishment offers enormous opportunities, in terms of regional labour markets and economic integration of a market with a large value of about US$2.6 trillion and over 622 million people. This research aims to study the characteristics of the "smart farmers" in the upper northern provinces of Thailand and to analyse their perceptions towards the AEC. The study's primary data were randomly collected from 400… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, Indonesia is considered to be incapable and has failed to face the AEC (Permatasari, 2020;Rahadyan & Lubis, 2018) . In addition, Yaakub et al, (2020) revealed that online entrepreneurship is still in scarcity, while Lin et al, (2018), and Maliki et al, (2020) reveal weaknesses in traditional businesses. Fadilla, (2019) argues that students currently face problems in making decisions when leaving school life, choosing majors, setting goals and carrying out social interactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, Indonesia is considered to be incapable and has failed to face the AEC (Permatasari, 2020;Rahadyan & Lubis, 2018) . In addition, Yaakub et al, (2020) revealed that online entrepreneurship is still in scarcity, while Lin et al, (2018), and Maliki et al, (2020) reveal weaknesses in traditional businesses. Fadilla, (2019) argues that students currently face problems in making decisions when leaving school life, choosing majors, setting goals and carrying out social interactions.…”
Section: Introductionmentioning
confidence: 99%